After.life [videorecording (DVD)] - Ricci, Christina; Long, Justin, 1978-; Neeson, Liam; Wojtowicz-Vosloo, Agnieszka (Distributed by Anchor Bay Entertainment, 2010)
After a terrible car accident, Anna wakes to find the funeral director is preparing her body for her own funeral. Convincing her that she is in transition to the afterlife, the funeral director is leading Anna to accept her own death. But Paul, Anna's grief-stricken boyfriend, can't shake the nagging suspicion that the funeral director is not what he appears to be. As Paul gets close to unlocking the truth, it may be too late as Anna may have already begun crossing over to the other side!